Fruit, vegetable, and legume intake and the risk of all-cause, cardiovascular, and cancer mortality: A prospective study. Issue 6 (June 2021) - Liu, Weida; Hu, Bo; Dehghan, Mahshid; Mente, Andrew; Wang, Chuangshi; Yan, Ruohua; Rangarajan, Sumathy; Tse, Lap Ah; Yusuf, Salim; Liu, Xiaoyun; Wang, Yang; Qiang, Deren; et al.
Summary: Background & aims: Although fruits and vegetable consumption has been shown to be associated with lower risks of mortality, cancers, and cardiovascular disease (CVD), there are limited data from China on the shape of the association. This study aimed to quantify the relationship between levels of fruit, vegetable, and legume consumption with the risk of major CVD, CVD mortality, cancer incidence, cancer mortality, and all-cause mortality. Methods: In the baseline survey, participants attended 1 of 115 (45 urban and 70 rural) communities from 12 provinces to complete a standardized questionnaire, and undergo a physical examination between 2005 and 2009, and were followed up till 2017 (for the current analysis). Diet was assessed through in-person interviews by using validated food-frequency questionnaires. The clinical outcomes were adjudicated centrally by trained physicians using standardized definitions. Cox frailty models were used to explore the associations between fruit, vegetable, and legume consumption with the risk of all-cause, CVD, and cancer mortality. Results: A total of 41 243 participants were eligible for inclusion in the analyses. The average combined average daily intake of fruit, vegetable, and legume was 2.97 [standard deviation (SD) 1.22] servings per day. During a median follow-up of 8.9 years [interquartile range (IQR) 6.7–9.9 years], we recorded 1893 major CVDs, 794 cancer events, and 1324 deaths, with 411 CVD deaths and 429 cancer deaths. In the models adjusted for age, sex, and center (random effect), a higher total intake of fruit, vegetable, and legume was inversely associated with CVD mortality, cancer incidence, cancer mortality, and all-cause mortality. After adjusting for additional covariates, the associations were evidently attenuated and only the association with all-cause mortality (hazard ratio [HR] trend 0.92, 95% CI 0.86–0.98, p trend = 0.021) remained significant, with a non-significant trend for major CVD (HR trend 1.02, 95% CI 0.97–1.08, p trend = 0.449), CVD mortality (HR trend 0.94, 95% CI 0.84–1.06, p trend = 0.301), cancer incidence (HR trend 0.97, 95% CI 0.89–1.06, p trend = 0.540), or cancer mortality (HR trend 0.92, 95% CI 0.82–1.04, p trend = 0.174). Compared with the reference group, the risk of all-cause mortality was the lowest for four to five servings of total daily intake of fruit, vegetable, and legume (HR 0.73, 95% CI 0.55–0.97), and did not show a further decrease for the higher intake group. Separately, fruit intake was associated with a lower risk of all-cause mortality (HR trend 0.92, 95% CI 0.86–0.99, p trend = 0.020) and legume intake was associated with a lower risk of major CVD (HR trend 0.95, 95% CI 0.90–0.99, p trend = 0.028) and all-cause mortality (HR trend 0.94, 95% CI 0.89–0.99, p trend = 0.020) in the fully adjusted models. Conclusions: This prospective study suggests that Chinese people with daily consumption of four to five servings (equivalent to 500–625 g/day) of fruit, vegetable, and legume demonstrated the lowest mortality, which conveys an encouraging message to the public that lifestyle modification to increase fruit, vegetable, and legume intakes may have greater beneficial effects on reducing all-cause mortality.